Records of Pauropoda (Pauropodidae, Brachypauropodidae, Eurypauropodidae, Sphaeropauropodidae) from China, with a key to the species and descriptions of three new species of Decapauropus - Qian, Changyuan; Dong, Yan; Bernard, Ernest C.; Sun, Hongying (Zootaxa, 2015)
The arthropod class Pauropoda was not recognized from China until 1988, but currently 36 known species are now recorded from 27 sites in 18 provinces. This paper contains descriptions of three new species of Decapauropus Remy, 1931: D. biclavula sp. n., D. annulcordatus sp. n. and D. tribulosus sp. n. from Jiangsu, Hunan, Jiangxi and Guangxi Provinces, respectively. These three new species bring the known pauropod fauna of China to 39 species in 11 genera and four families. In addition, Dasongius (Sun & Guo, 2010) nom. nov. is proposed to replace the invalid junior homonym of Songius Sun & Guo, 2010.